Climate Caracteristic and Childhood Pneumonia: Systematic Review - Anni Fithriyatul Mas’udah; Terry Yuliana Rahadian Pristya (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2020)
Backgrounds: Pneumonia is the leading cause of death in children worldwide. Pneumonia is the cause of mortality in an estimated of 922,000 children under age 5 in 2015, accounting for 15% of all deaths of children under five years old. The climatic conditions are complex and varied, had pneumonia a different impact in each country. The purpose of this study is to address the relationship between complications and childhood pneumonia. Methods: This research was a systematic review of the study literature. The review method follows the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) checklist 2009. The number of articles that match the keywords is 254 articles and 8 articles that can be used. Results: Seven of eight article's differences show the relationship between characteristics and pneumonia in children. Conclusions: There is a relationship with the characteristics of pneumonia in children. (J Respir Indo. 2020; 40(1): 58-65)